Developing Typical Template Portal for Educational Institutions inKyrgyz Republic - C. Baizhanova; U. Brimkulov (MANAS: Journal of Engineering)
With the using ICT and application of open network resources is changing the pace and perspectives. Web systems for school was predicted to streamline schools processes, responsibilities internally of personnel and pupils and externally community expectations. Consequently problem of development site template of Kyrgyzstan educational institutions was produced. A defination of information system, informatization of education were given. This paper presents with the research method in the technical and information aspects 100 and more school web based systems of foreing countries and Kyrgyzstan analysis. A function and structure of the site template were created. Advantages web based systems were described.